Complete resolution of non‐necrotizing lung granuloma and pyoderma gangrenosum after restorative proctocolectomy in a woman with severe ulcerative colitis and cytomegalovirus infection. Issue 2 (2nd January 2016) - Sartini, Alessandro; Bianchini, Marcello; Schepis, Filippo; Marzi, Luca; De Maria, Nicola; Villa, Erica
Key Clinical Message: Here, we report the unusual case of an ulcerative colitis female patient presenting together with cytomegalovirus infection, pyoderma gangrenosum and a noncaseating lung granuloma, both resistant to immunomodulatory drugs which dramatically obtained a clinical stable remission after restorative proctocolectomy. Abstract : Here, we report the unusual case of an ulcerative colitis female patient presenting together with cytomegalovirus infection, pyoderma gangrenosum, and a noncaseating lung granuloma, both resistant to immunosuppressive therapies, which dramatically obtained a clinical stable remission after restorative proctocolectomy.